Fertilidade do solo, produtividade de cana soca e residuos póscolheita afetados pela aplicação superficial de calcário e gesso na região sudeste do Brasil - Rossato, Otavio Bagiotto; Foltran, Rodrigo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Martello, Jorge Martinelli [UNESP]; Rossetto, Raffaella; McCray, James Mabry (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
The aim of this study was to evaluate soil fertility amendment, stalk yield, sugar, bagasse, and trash yield as affected by surface application of dolomitic limestone and gypsum in green sugarcane ratoon. A factorial arrangement of four dolomitic limestone rates (0, 900, 1800, and 3600 kg ha–1) and two gypsum rates (0 and 1700 kg ha–1) was used in the experiment. The experiment was performed from October 2006 to October 2007, starting in the rainy season after the 2nd ratoon harvest of the variety SP813250 in a commercial green sugarcane plantation of the São Luiz Sugar Mill (47º25'33 W; 21º59’46”, 627 m of altitude), located in Pirassununga, state of São Paulo, in southeast Brazil. After 12 months, the experiment was harvested, technological measurements of stalk yield were made, and soil samples were taken and analyzed. Gypsum acts as a subsurface conditioner thus contributing so the benefits of surface limestone application, on soil acidity correction, to reach deeper layers, allowing the development of the root system of plants in greater depth. However, application of gypsum may lead to leaching of Mg and K from the topsoil layers. The higher rates of lime in surface application provided acidity amendment and, consequently, increased soil fertility in the soil profile, and increased sugarcane stalk, sugar, bagasse, and trash yield.
Soil fertility, ratoon sugarcane yield, and post-harvest residues as affected by surface application of lime and gypsum in Southeastern Brazil
Keywords: Bagasse and trash; Sacharum spp; Soil chemical properties; Stalks; Sugar